USING “TABOO GAME” AS A TECHNIQUE TO TEACH SPEAKING DESCRIPTIVE TEXT TO THE SEVENTH GRADERS OF SMPN 33 SURABAYA (RETAIN, 2016)
USING “TABOO GAME” AS A TECHNIQUE TO TEACH SPEAKING DESCRIPTIVE TEXT TO THE SEVENTH GRADERS OF SMPN 33 SURABAYA Ajeng Awidianingrum English Department, Languages and Arts Faculty, The State University of Surabaya Email: ajengawidianingrum@gmail.com Ririn Pusparini, S.Pd, M.Pd English Department, Languages and Arts Faculty, The State University of Surabaya Email: rrn.puspa@gmail.com Abstract This study aims to describe the implementation of Taboo game to teach speaking descriptive text to the seventh graders of SMPN 33 Surabaya. This study also described the students’ responses and the students’ speaking performances toward the use of Taboo game. This study is a qualitative research, the data of which were collected through observation checklist, interview sheet and speaking performance task. The observation was done in two meetings. The interview sheet was given in the last of the first meeting and the speaking performance task was done in the second meetings. The speaking performance task is only given as the performance capabilities not as a test. The observation checklist was analyzed by checking the teacher ways in implementing Taboo game as a technique to teach speaking descriptive text. Then, the interview sheet was analyzed based by describing the result of the interview sheet given by the researcher to all of the students. The researcher used the speaking scoring rubric from Harris (1969) to analyze the speaking performance task. The observation result shows that the teacher made some modifications of the Taboo game’s roles from Cervantes (2009). Moreover, the result of the interview sheet shows that the students response positively toward the implementation of Taboo game. In addition, the students show their best speaking performances in describing an animal based on the result of the speaking performance task. Keywords: Speaking, Descriptive text, Taboo game Abstrak Penelitian ini bertujuan untuk mendeskripsikan penggunaan Taboo game untuk mengajar kemampuan berbicara dalam teks deskriptif untuk siswa kelas VII di SMPN 33 Surabaya. Penelitian ini juga menjelaskan tanggapan para siswa dan penampilan berbicara siswa terhadap penggunaan Taboo game. Penelitian ini merupakan penelitian kualitatif. Data yang dikumpulkan melalui lembar pengamatan, lembar wawancara dan tugas penampilan berbicara. Pengamatan dilakukan dalam dua pertemuan. Lembar wawancara diberikan akhir dari pertemuan pertama dan tugas penampilan berbicara dilakukan dalam pertemuan kedua. Tugas penampilan berbicara hanya diberikan sebagai tugas kemampuan dalam berbicara tidak sebagai ujian. Lembar pengamatan dianalisis dengan memeriksa cara guru dalam menggunakan Taboo game sebagai teknik untuk mengajar kemampuan berbicara dalam teks deskriptif. Kemudian, lembar wawancara dianalisis dengan mendeskripsikan hasil dari lembar wawancara yang diberikan oleh peneliti untuk semua siswa. Peneliti menggunakan rubrik penilaian berbicara dari Harris (1969) untuk menganalisis tugas penampilan berbicara. Hasil pengamatan menunjukkan bahwa guru membuat beberapa modifikasi dari aturan dalam Taboo game yang berasal dari Cervantes (2009). Selain itu, hasil lembar wawancara menunjukkan bahwa siswa memberikan respon positif terhadap pelaksanaan Taboo game. Selain itu, siswa menunjukkan penampilan terbaik mereka dalam mendeskripsikan binatang berdasarkan hasil dari tugas penampilan berbicara. Kata Kunci: Berbicara, Teks deskriptif, Permainan Taboo